Surgical problems of the hydatic cysts of the pouch of Douglas - Gonzalez Vales, Horacio; Crestanello, Francisco A. (Cirugía del Uruguay, 1971)
The paper discusses the problems with which the surgeon is faced in cases of hydatid cysts of the pelvis with reference to diagnosis; complementary tests; its anatomic relation with vascular and peritoneal víscera and elements. The importance of the anatomic condition of the cyst, whether it is calcified or not and its prolongations by exogenous vesiculization. Finally to surgical tactics either through drainage (cystostomy) or complete ar almost total resection, including the technical difficulties which the latter presents. The author concludes that better postoperatory results of cystectomy compensate its technical difficulties.